Peripheral blood expression of nuclear factor-kappab-regulated genes is associated with rheumatoid arthritis disease activity and responds differentially to anti-tumor necrosis factor-alpha versus methotrexate - Parker, Alex; Izmailova, Elena S; Narang, Jigna; Badola, Sunita; Le, Tinh; Roubenoff, Ronenn; Ginsburg, Geoffrey S; Maier, Agnes; Coblyn, Jonathan S; Shadick, Nancy A; Weinblatt, Michael E (Journal of rheumatology, 2007)
To evaluate peripheral blood expression of genes regulated by nuclear factor-kappaB (NF-kappaB), a key mediator of tumor necrosis factor-alpha (TNF-alpha) signaling, in patients with rheumatoid arthritis (RA) before and during treatment with anti-TNF-alpha or methotrexate (MTX). We analyzed association of gene expression with disease activity, rheumatoid factor (RF), age, sex, disease duration, treatment modality, and clinical response. Sixty patients consented for RNA analysis at baseline and after 2 and 6 weeks of treatment. Disease activity was quantified using Disease Activity Score (DAS28) and C-reactive protein (CRP). Expression of 67 TNF-alpha-responsive, NF-kappaB-regulated genes was measured using Affymetrix arrays and RT-PCR. Expression of 34 genes was associated with DAS28-CRP, notably S100A12/calgranulin C, IL7R, and aquaporin 3. No association was observed with age, sex, RF, or disease duration. Expression of 16 genes changed in a manner that differed significantly between treatment groups. Eleven were reduced in anti-TNF-alpha-treated patients relative to MTX, while 5 were increased. The majority of these observations were confirmed using RT-PCR. Gene expression was not associated significantly with change in disease activity. NF-kappaB-dependent gene expression in peripheral leukocytes is highly correlated with RA activity as measured by DAS28-CRP. Expression of many genes responds differentially to anti-TNF-alpha versus MTX, suggesting fundamentally different effects on the NF-kappaB pathway. This peripheral blood expression signature provides candidate markers that could lead to development of a simple, minimally invasive pharmacodynamic assay for RA treatments directed at the NF-kappaB pathway. Combination of gene expression data with clinical scores and serum markers may provide more sensitive and predictive measures of RA disease activity.